MATERIALS FOR DEVELOPING STUDENTS' LANGUAGE COMPETENCE IN NATIVE LANGUAGE CLASSES - Tajbenova Saule Sarsengalievna (Web of Journals Publishing, 2025)
In this article, language competence in lower grades is developed through conscious assimilation of language rules and their correct application in practice. The main task of supervision is aimed at systematic assessment of students' knowledge and skills in each section of language rules and their improvement.
Keywords: Language competence, rule, education, memory, competence, competence, traditional, knowledge, skill, imagination.